Association of RENAL nephrometry score with outcomes of minimally invasive partial nephrectomy. (6th November 2012) - Ellison, Jonathan S; Montgomery, Jeffrey S; Hafez, Khaled S; Miller, David C; He, Chang; Wolf, J Stuart; Weizer, Alon Z
Abstract : Objective: To evaluate the predictive value of the Radius, Exophytic, Nearness, Anterior, Location nephrometry scoring system and to investigate the influence of its individual components on perioperative outcomes of minimally invasive partial nephrectomy. Methods: Consecutive laparoscopic partial nephrectomy ( n = 189) and robotic partial nephrectomy ( n = 109) cases from 2007 through 2011 were retrospectively reviewed from our prospectively maintained database. Urological surgeons assigned nephrometry scores, excluding cases without images available for review. The association of nephrometry score categories and individual components of the score to perioperative outcomes were assessed. Results: No differences were observed in preoperative characteristics of low ( n = 135), intermediate ( n = 155) and high ( n = 8) nephrometry groups. Higher nephrometry score was associated with an increased length of stay, estimated blood loss and warm ischemia time. Higher nephrometry scores were also associated with a greater proportion of major complications ( P < 0.001). Distance to the renal sinus had the greatest impact on perioperative outcomes including operative and ischemic times, estimated blood loss, complications and length of stay. Conclusions: The Radius, Exophytic, Nearness, Anterior, Location nephrometry score has value as a predictive tool for perioperative outcomes of minimally invasive partial nephrectomy. Distance to the renal sinus seems to have the greatest association with outcomes. Using these findings, clinicians will be better able to counsel patients regarding anticipated perioperative outcomes of minimally invasive partial nephrectomy.